Pengaruh Teknologi, Lingkungan, Melalui Social Media Adopction terhadap Business Peformance UMKM di Kota Kendari - Nurwati Nurwati; Husin Husin (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to examine the influence of technology and environment on business performance through the mediation of social media adoption among MSMEs in Kendari City. A quantitative approach was applied using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) through the SmartPLS 4.0 software. The research sample consisted of 100 MSME actors selected using purposive sampling techniques. The results show that technology and environment have a positive and significant effect on social media adoption. Furthermore, social media adoption has a positive and significant effect on MSMEs' business performance. However, the direct influence of technology on business performance was not significant, indicating that social media adoption plays a crucial mediating role in this relationship. Therefore, this study confirms that the utilization of technology, supported by the adoption of social media, can effectively improve the business performance of MSMEs.